CAN VILLAGE FUNDS STRENGTHEN ECONOMIC GROWTH IN INDONESIA? - Herdiyana, Deni; Sugiyanto, Hari; Sutarto; Andriana, Nina (Polytechnic of State Finance STAN, 2025)
This research aims to determine the influence of village funds on economic growth in Indonesia, with General Allocation Funds (DAU), Special Physical Allocation Funds (DAK Fisik), Profit Sharing Funds (DBH), Village Fund Allocations (ADD), Social Protection Spending as control variables. This research was conducted using quantitative methods through panel data regression in order to analyze the data. The research found that Village Funds as the main independent variable have a very significant positive influence on the dependent variable, namely economic growth (GRDP). This study suggests that Village Fund transfers should continue, because these funds play an important role in encouraging economic growth in Indonesia. Keywords: village funds, economic growth, DAU, DAK Physics, DBH, Social Protection Spending